Board composition in federated structures: a case study of the Gaelic Athletic Association. Issue 2 (2nd April 2016) - O'Boyle, Ian; Hassan, David
ABSTRACT: This paper examines the issue of board composition within non-profit sport organizations operating in a federated governance structure. The Gaelic Athletic Association (GAA) is used as a case study to illustrate the challenges and complexities of comprising a board that has the requisite skill set to carry out its function in a rapidly changing operating environment. Interviews ( n  = 10) supported by document analysis were conducted with senior ranking officials within the Association in order to analyse the integral factors related to board composition within the GAA. Findings show that the Association heavily relies on the delegate system of board composition, potentially limiting its ability to appoint a board that has a commercially orientated focus reflecting the professionalization and commercialization of the contemporary sport industry. Practical and theoretical implications of these findings are discussed along with suggestions for future research.